Eksplorasi Media Interaktif Wordwall Topik Lingkunganku dalam Mengembangkan Kemampuan Bahasa Anak di TK PKK Jalmak Pamekasan - Prastyo, Danang; Rosyanafi, Rofik Jalal; Iftitah, Selfi Lailiyatul; Reswari, Ardhana; Anggraini, Denok Dwi; Wahyuni, Wahyuni (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
The goal of early childhood education (PAUD) is to provide the best possible education and stimulation for children from birth to age six. Language development is one area that needs improvement. This study looks into how Wordwall games might help PKK Jalmak Kindergarten's young students' language development. Qualitative descriptive method was used in this study and involved 19 children from group A of TK PKK Jalmak, aged between 4 and 5 years old, consisting of 8 girls and 11 boys. Observation, interview, and documentation were the methods used to collect data. The results showed that the Wordwall game requires various steps, such as planning and preparation, implementation, and evaluation. All of these steps are characterized by improvements in letter recognition, repeating new vocabulary, the ability to understand two simple instructions, and the ability to identify words according to pictures.